THE POLITICS OF THE JUDGES: THE GOVERNMENT OF THE JUDICIAL POWER IN POLITICAL SYSTEMS. A STUDY OF THE COUNCIL MODEL - Casal Oubiña, Daniel (2024)
One of the elements least analyzed by Political Science and Public Administration lies in the study of the judiciary as a true power of the State whose decisions, in addition to legal significance, have an important social and political repercussion. This work focuses on the government of the judiciary, analyzing the different typologies that exist and studying 12 cases in which the judiciary council model is chosen. The study examines key aspects such as the nature of the council to understand its institutional affiliation in the system, the election processes of its members as well as its governing bodies and finally its competence framework for action, detecting similarities as well as important differences between the systems analyzed.